THE ATTITUDES OF MEDICAL STUDENTS TOWARDS CLINICAL RELEVANCE OF HISTOLOGY - Naureen Waseem; Aaqiba Rasheed; Maria Gill; Ayesha Asad; Muhammad Omar Shamim; Fatima Waseem (Pakistan Armed Forces Medical Journal, 2021)
Objective of Study: